Cloud-based Electronic Health Records (EHR) adoption rate in Nigeria: barriers and performance bottlenecks - Olumhense Adoghe; Braimoh Ikharo; Henry Amhenrior (BMC Digital Health, 2026)
Abstract Background While cloud-based Electronic Health Records (EHRs) are crucial to improving service quality and operational efficiency, uptake is still variable across low-income and middle-income countries (LMICs). There is a significant research gap in Nigeria in terms of empirical evidence on the actual maturity of the implemented systems and the specific performance constraints affecting the effective use of the system. Aim This study aimed to assess the adoption status and operational maturity of EHR systems in Nigerian healthcare facilities. Methods An exploratory sequential mixed methods design was used for this study to diagnose the EHR landscape in Nigeria. Primary data were collected through a structured survey of 26 healthcare facilities in 11 states and secondary institutional data were obtained from 130 facilities to serve as a national baseline. The analysis included descriptive statistics, Chi-square tests (χ²) and systems-engineering tools, such as Pareto analysis, Fishbone (Ishikawa) diagrams and the Technology Acceptance Model (TAM) framework, for prioritizing bottlenecks and assessing user acceptance. Results A substantial ‘socio-technical gap’ was found: though 75% of the facilities in the secondary dataset had installed digital systems, the primary survey showed that only 23% had fully electronic systems and 42% were stuck in ‘hybrid’ processes. Pareto analysis highlighted power instability (76.9%), high implementation costs (69.2%) and poor IT infrastructure (65.4%) as the “vital few” barriers contributing more than 80% of the underperformance of systems. However, overall staff satisfaction was relatively high (57.7%) with reported challenges being infrastructure and system reliability. This finding suggests that healthcare professionals may recognize the value of EHR systems despite infrastructural challenges affecting their use. Conclusions The adoption of EHR in Nigeria is in a transition phase with institutional ambitions often being obstructed by a fragile infrastructure envelope. The identified bottlenecks will be resolved through a comprehensive approach, including localization as a cloud hosting solution to reduce the economic risks, ‘green’ measures to address power generation and national interoperability standards to address data-sharing and system fragmentation. The results offer a scientific and evidence-based pathway to speed up digital health transformation in lower-resource settings.